Primary Ciliary Dyskinesia in Children - Alexander A. Baranov; Leyla S. Namazova-Baranova; Elena A. Vishneva; Liliya R. Selimzyanova; Maiya D. Bakradze; Elena N. Tsygina; Anna V. Lazareva; Lyudmila K. Katosova; Yuliya V. Gorinova; Оlga V. Kustova (Педиатрическая фармакология)
The article presents current approaches to medical care delivery in children with primary ciliary dyskinesia. The genetic heterogeneity of the disease causes the variability of pathological symptoms in clinical practice. The most common clinical manifestation in children is the frequent inflammatory diseases of the upper and lower respiratory tract which are registered in the majority of patients, especially in young children. However, the diagnosis is often untimely due to the low disease awareness among medical specialists. The article describes the algorithm for differential diagnostic search in detail, presents approaches to the treatment and management of pediatric patients with primary ciliary dyskinesia. The material is based on clinical recommendations developed and approved by the professional association «Union of Pediatricians of Russia»; recommendations were updated in 2018.